A practical approach to bank lending - Dyer, L. S.; Institute of Bankers (Great Britain) (London : Institute of Bankers, 1977)
The book examines processes of bank lending. The main types of lending problems encountered by clearing bankers and ways to resolve them.
Includes index.
usc 25/05/2017
Loans
Keywords: Bank loans